2011
DOI: 10.1136/bcr.01.2011.3682
|View full text |Cite
|
Sign up to set email alerts
|

Lower lip numbness in a patient with colorectal cancer

Abstract: BACKGROUNDMetastatic lesions to the mandible are rare, comprising less than 1% of all malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…To better understand the association between oral cavity metastases and colon cancer, 12 cases of oral cavity metastases of colon cancer, including the present case, were reviewed [6,7,[10][11][12][13][14][15][16][17][18]; Table I]. It was observed that mandibular metastases from colon cancer regularly occurred the sixth and seventh decades of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the association between oral cavity metastases and colon cancer, 12 cases of oral cavity metastases of colon cancer, including the present case, were reviewed [6,7,[10][11][12][13][14][15][16][17][18]; Table I]. It was observed that mandibular metastases from colon cancer regularly occurred the sixth and seventh decades of life.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic oral tumors are rare, contributing to ~1% of all oral tumors (7). Theoretically, all types of tumors may metastasize to the oral cavity, the most common primary organs being the lungs in men and the breast in women.…”
Section: Introductionmentioning
confidence: 99%
“…The numb lower lip periodically presents as a manifestation, and even presenting symptom, of malignant disease. Review of the recent literature reveals that the causative tumours are diverse: mandibular central mucoepidermoid carcinoma, leukaemia, breast cancer, colorectal cancer, osteosarcoma, as well as two lymphomas which have presented to the author during 20 years of clinical practice. Lung adenocarcinoma is the most common cell type in females (smokers and non‐smokers).…”
Section: Discussionmentioning
confidence: 99%